1997
DOI: 10.1038/386843a0
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin is essential for integrin-mediated calcium signalling and cell adhesion

Abstract: Integrins are important mediators of cell adhesion to extracellular ligands and can transduce biochemical signals both into and out of cells. The cytoplasmic domains of integrins interact with several structural and signalling proteins and consequently participate in the regulation of cell shape, motility, growth and differentiation. It has been shown that calreticulin associates with the cytoplasmic domains of integrin alpha-subunits and that this interaction can influence integrin-mediated cell adhesion to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
288
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 365 publications
(303 citation statements)
references
References 27 publications
11
288
2
Order By: Relevance
“…Akt activation or inactivation has been reported to play an important role in CRT-associated apoptosis (Kageyama et al, 2002;Okunaga et al, 2006;Lim et al, 2008). CRT-deficient mice show embryonic lethal characteristics due to changes in cell adhesiveness and impairment of cardiac development and function (Coppolino et al, 1997;Rauch et al, 2000;Mesaeli and Phillipson, 2004). CRT may have an important role in the development and/or progression of various human cancers: overexpression of CRT has been found in breast ductal carcinoma (Bini et al, 1997;Chahed et al, 2005), prostate adenocarcinoma (Alaiya et al, 2000), hepatocellular carcinoma (Kim et al, 2004) and colon cancer (Vougas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Akt activation or inactivation has been reported to play an important role in CRT-associated apoptosis (Kageyama et al, 2002;Okunaga et al, 2006;Lim et al, 2008). CRT-deficient mice show embryonic lethal characteristics due to changes in cell adhesiveness and impairment of cardiac development and function (Coppolino et al, 1997;Rauch et al, 2000;Mesaeli and Phillipson, 2004). CRT may have an important role in the development and/or progression of various human cancers: overexpression of CRT has been found in breast ductal carcinoma (Bini et al, 1997;Chahed et al, 2005), prostate adenocarcinoma (Alaiya et al, 2000), hepatocellular carcinoma (Kim et al, 2004) and colon cancer (Vougas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…5,7 CRT is a Ca 2 þ -binding protein with two sites (with high and low capacity) for buffering Ca 2 þ , thus affecting Ca 2 þ signaling and Ca 2 þ homeostasis. [8][9][10] CRT is a soluble protein Received 31.1.08; revised 17.3.08; accepted 31.3.08; Edited by P Bouillet; published online 9.5.08 …”
mentioning
confidence: 99%
“…More recently, we demonstrated that murine embryonic stem cells genetically lacking calreticulin exhibit severely impaired integrin-mediated adhesion and calcium influx [31]. In the present study, we have used PC-3 prostatic carcinoma cells to demonstrate that calreticulin interacts transiently with integrins as the cells attach and spread on ECM proteins.…”
Section: Introductionmentioning
confidence: 62%
“…It was also found that this induced interaction between the integrin and calreticulin is important for the α # β " -mediated adhesion of Jurkat cells to collagen type I [30]. More recently, we reported on the development of calreticulin knock-out murine embryonic stem cells, and found that calreticulin is essential for integrin-mediated adhesion and calcium signalling [31]. The results of the present study suggest that calreticulin binds to integrins as they first become activated, either by antibody stimulation or by encountering ECM proteins.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation